THE INFLUENCE OF STRENGTH TRAINING OF GROWTH AND DEVELOPMENT OF SUBADOLESCENT AND EARLY ADOLESCENT CHILDREN - Branislav Radulović; Goran Gojković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Today 's children are engaged by things which don't cause enough irritation for quality development of skelton-muscle system. There's a common opinion that strength training for subadolescent and early adolescent children is very harmful and useless. However; a lot of examinations show that a good invented progress of strength training is resulting increasing of muscle strength; ligament strength and insuring the bases of right growth and development of children: the quality strenght training enables a child to face better everyday' s efforts. It's also important fact of optimal psyzical preparation which is necessary for the further sport development.